WARALABA MODEL BISNIS BARU YANG BERKELANJUTAN DITINJAU DARI ASPEK HUKUM - Hudiarini, Sri; Kartiko, Galuh; Mundzir, Hudriyah (Fakultas Hukum Universitas PGRI Kanjuruhan Malang, 2018)
Today the growth of the business world is growing so rapidly, it is also supported to expand the business which is more varied, including through franchise (Franchise). Which of these principles for some entrepreneurs is considered more effective, effective and profitable in the development of a business. In Indonesia, the regulation of franchises is based on agreements made by the parties on the basis of the applicable law, in this case the Government Regulation and the Minister of Trade Regulation. Franchise is a form of business that gets a lot of attention from business people, because it can be one way to increase economic activity and give opportunity to weak economic class to try, this means, Franchise can provide job opportunity, equality and also create field work for the community. In addition, the profits of this business are low cost and the materials already provided are also not too take place so vast, franchise recipients no longer need to bother developing their business by building a good and famous image. It is enough to ride on the famous fame of the franchisor, so franchisees who are generally small entrepreneurs will enjoy the success and luck of large-scale companies without having to carry out their own research and development, marketing and promotion that usually requires enormous expenses that the small businessman is unlikely to bear.